Phantom thief Jeanne. Vol. 3 - Tanemura, Arina (Viz Media, 2014)
"A stranger has witnessed Jeanne's transformation, and Maron worries that the police will soon find out her real identity. Chiaki again asks Maron to go out with him, but she refuses because they are on opposing sides. But if Chiaki is truly her enemy, why is he asking his partner, Access, if he's been working for the Demon Lord?" --